THE EFFECT OF HOMALANTHUS POPULNEUS (GIESEL.) PAX. EXTRACT IN EXPRESSION OF T-CELL RECEPTOR: INHIBITION STUDY OF HIV INFECTION - E., SINTYA; N., WIJAYANTI; A., NORAENI (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of this study is to analyze the effect of Homalanthus populneus’s extract toward the expression of CD4 and CD8 which both are important in body’s defense mechanism against HIV. Methods: Leaves and barks of H. populneus were extracted with 70% ethanol. Freeze dry method had been used in order to get the final extract. PBMCs were extracted and it has been used for CD4 and CD8 expression test using flow cytometry. In oreder to analyze the effect of the extract to the HIV type 1, gp41 and gp120 expression was tested using talicytometry and using enzyme-linked immunosorbent assay, respectively. Results: This study reported that H. populneus’s extract reduced the expression of CD4 receptor in both peripheral blood mononuclear cell (PBMC) and T-lymphoblast cell line (CEM). In contract, this extract increased CD8 expression in PBMC. It was also able to reduce the percentage of protein gp41 and gp120 in CEM cultures. Conclusion: Those results show that H. populneus’s extract is potentially developed as an HIV drug from Indonesia. However, further study needs to be done including analyzing the effect of variety of concentrations and also exposure periods.